Harmonizing Conservation Values of National and Customary Laws on Turtles Conservation - Muhammad Yamani (Jambe Law Journal, 2019)
Sea turtle populations on the Enggano Island are almost extinct as a result of over exploitation. This article aims to discuss harmonization of conservation values between national law and Enggano customary people in protectng sea turtles. It is found that the Enggano customary law norms have conservation values which stated prohibition of catching sea turtles by any means except for adat grandeur ceremonies (yakadea) use only. Sanctions are imposed to those who break the law with customary ﬁnes and a compulsary to apology to the chiefs and other Enggano Island communities. It is also learned that to harmonize conservation values between national law and Enggano customary law in protecting sea turtles can be conducted by implementing the norms of turtle protection in the national laws into the Village Regulation, which is an integral part of the hierarchical systems of laws and regulations in Indonesia. Harmonization of the conservation values of the sea turtles through the integration of legal substance is the best model in optimizing the protection of sea turtles without sacriﬁcing the interests of traditional rituals that are still maintained for generations in the life of the Enggano community